Optimization of Compressive Strength and Porosity of Normal Concrete Using Fly Ash and Alkaline Activators - Wahyu Kartini; Made Dharma Astawa; Hendra Setiawan (Kadiri University, 2022)
The use of cement in the concrete mix is the most expensive material. In the cement production process, there is CO2 emission into the air, which causes the greenhouse effect and global warming. So we need other materials as an alternative to reduce the use of cement by using by-products such as fly ash which is categorized as a Pozzolan material. In this study, fly ash was used with variations of 0%, 70%, 80%, 90%, 100%, water-cement ratio 0.4. Because fly ash does not have the same binding ability as cement, alkaline activators are needed, namely Sodium Silicate (Na2SiO3) and Sodium Hydroxide (NaOH) Â , with molarities of 6M and 8M. To determine the compressive strength of concrete, a compressive test was carried out at the age of 7 days and 28 days and a porosity test at the age of 28 days. The maximum compressive strength of concrete with fly ash content of 90% with a molarity of 6M and 8M. The age compressive strength has the same value. At the age of 7 days is 14.43 MPa. At the age of 28 days, it is 18.39 MPa. The greater the use of fly ash and molarity in concrete, the fewer pores in the concrete because the mixture is more concentrated and round, and the small particle size of fly ash can fill voids in the concrete.